Needs for care of residents with schizophrenia spectrum disorders and association with daily activities and mood monitored with experience sampling method: the DIAPASON study. (11th April 2023) - Martinelli, Alessandra; D'Addazio, Miriam; Zamparini, Manuel; Thornicroft, Graham; Torino, Gabriele; Zarbo, Cristina; Rocchetti, Matteo; Starace, Fabrizio; Casiraghi, Letizia; Ruggeri, Mirella; de Girolamo, Giovanni
Abstract: Aims: Care needs represent an essential paradigm in planning residential facility (RF) interventions. However, possible disagreements between users and staff are critical issues in service delivery. The Experience Sampling Method (ESM) tracks experiences in the real world and real time. This study aimed to evaluate the care needs of patients with schizophrenia spectrum disorder (SSD) in RFs and its association with daily activities and mood monitored using the ESM. Methods: As part of the DIAPASON project, 313 residents with SSD were recruited from 99 Italian RFs. Sociodemographic and clinical characteristics were recorded. Care needs, the severity of symptomatology and negative symptoms were assessed. Fifty-six residents were also assessed for 7 consecutive days using the mobile ESM. Descriptive, agreement, predictor and moderator analyses were conducted. Results: The staff rated a higher number of total and met needs than service users ( p < 0.001). Only a slight agreement between users and staff on unmet needs was found in self-care ( k = 0.106) and information ( k = 0.100) needs, while a moderate agreement was found in accommodation ( k = 0.484), food ( k = 0.406), childcare ( k = 0.530), physical health ( k = 0.470), telephone ( k = 0.458) and transport ( k = 0.425) needs. Older age (−0.15; p < 0.01), longer SSD diagnosis (−0.16; p < 0.01), higher collaboration (−0.16; p < 0.01) and lower symptomatology (−0.16; p < 0.01) decreased the number of unmet needs, while being a female (0.27; p < 0.05) and a shorter length of stay in an RF (0.54; p < 0.001) increased the number of unmet needs. A higher number of unmet needs was associated with a lower amount of time spent in leisure activities or reporting a positive mood: on the contrary, more unmet needs were associated with a greater amount of time spent in religious or non-productive activities. The associations between unmet needs rated by staff and users and momentary mood as assessed using the ESM were not moderated by the severity of symptomatology. Conclusions: Although care needs are fundamental in planning residential activities aimed at recovery-oriented rehabilitation, RF interventions did not fully meet users' needs, and some disagreements on unmet needs between users and staff were reported. Further efforts are necessary to overcome Italian RF limits in delivering rehabilitative interventions defined by real users' needs to facilitate users' productivity and progress towards personal recovery.